ESKALASI KETERAMPILAN KOMUNIKASI SISWA MELALUI METODE SUGGESTOPEDIA DALAM MENGEMBANGKAN KUALITAS BELAJAR - Muhammad Mushfi El Iq Bali; Sayyidatul Arifa (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
Abstract: Communication skills are the most important skills in students' daily life, related to the learning climate, and are very much needed as an independent matter in learning. Communication skills greatly facilitate educators and students in learning situations effectively and efficiently. This study aims to determine the quality of the communication skills of educators to students by applying suggestopedia in developing the quality of learning. Suggestopedia is a breakthrough for students in learning to be more positive, enthusiastic, and active in providing good stimulation to the learning process in order to create a more pleasant feeling. The research method used is descriptive qualitative method. This research was conducted at Madrasah Ibtidaiyah Walisongo, Banyuanyar Tengah, Probolinggo, with the research subjects being teachers and students. This research phase is carried out with preliminary studies (interviews), data collection, data verification, and drawing conclusions. The results of the study indicate that in its application, suggestopedia at the basic level has a dominant positive side impact. A conducive learning atmosphere, communication skills, effectiveness, and enthusiasm of students during learning can be seen that students' self-confidence is now increasing at each lesson meeting. The application of the suggestopedia method is essentially effective in carrying out the quality of learning.